Clinical characteristics and treatment response of chronic disseminated candidiasis in patients with hematological disorders - Zhangjie Chen; Sisi Zhen; Jiali Sun; Lukun Zhou; Tingting Zhang; Yuyan Shen; Wenjing Guo; Yizhou Zheng; Fengkui Zhang; Yingchang Mi; Lugui Qiu; Xiaofan Zhu; et al. (Scientific Reports)
Abstract Chronic disseminated candidiasis (CDC) is an invasive fungal infection typically affecting patients with hematological diseases and severe neutropenia, associated with increased mortality. However, there is a global shortage of clinical evidence on CDC. We retrospectively analyzed clinical data from 49 CDC patients over the past decade. Clinical characteristics of primary hematological diseases, CDC diagnosis, treatment and response evaluations were included. Clinical factors associated with CDC remission and patients’ survival were analyzed. The majority of patients had hematological malignancies (n = 43, 87.8%), and 27 patients (55.1%) had persistent severe neutropenia for more than 10 days prior to CDC. CT scans revealed liver lesions in 44 patients, spleen lesions in 34 patients, and kidney lesions in 9 patients. Proven, probable and possible CDC was diagnosed in 5 (10.2%), 3 (6.1%) and 41 patients (83.7%), respectively, and treatment outcomes at 3 months included 5 complete response (CR, 10.2%), 34 partial response (PR, 69.4%) and 10 treatment failure (20.4%). Caspofungin treatment showed a trend towards improving CR/PR rate, while severe neutropenia > 20 days and proven diagnosis were significantly associated with 3-month treatment failure. Kaplan–Meier curve showed achieving CR/PR within 3 months did not significantly prolong OS compared to treatment failure patients (1197.6 days vs. 564.8 days, P = 0.074). Additionally, no patient deaths were directly attributed to CDC infection. Age > 45 years old and malignancy non-remission were prognostic factors of overall survival (OS). Furthermore, a prediction model identified severe neutropenia > 20 days, proven/probable diagnosis and concomitant bacteremia as risk factors to effectively predict treatment failure. Also, patients with a risk score < 0.203 in the model exhibited more rapid treatment response. After CDC symptoms onset, lymphocyte levels remained consistently higher in treatment failure patients, while the neutrophil-to-lymphocyte ratio was persistently higher in CR/PR patients. Our findings recommend CT scans for diagnosis and caspofungin as first-line therapy while continuing scheduled chemotherapy or bone marrow transplantation. Notably, risk factors identified by the prediction model could be used to predict treatment response.